Phase‐Transformation‐Induced Giant Deformation in Thermoelectric Ag2Se Semiconductor. (13th September 2021) - Liang, Qi; Yang, Dongwang; Xia, Fanjie; Bai, Hui; Peng, Haoyang; Yu, Ruohan; Yan, Yonggao; He, Danqi; Cao, Shaowen; Van Tendeloo, Gustaaf; Li, Guodong; Zhang, Qingjie; et al.
Abstract: In most semiconducting metal chalcogenides, a large deformation is usually accompanied by a phase transformation, while the deformation mechanism remains largely unexplored. Herein, a phase‐transformation‐induced deformation in Ag2 Se is investigated by in situ transmission electron microscopy, and a new ordered high‐temperature phase (named as α ′‐Ag2 Se) is identified. The SeSe bonds are folded when the Ag + ‐ion vacancies are ordered and become stretched when these vacancies are disordered. Such a stretch/fold of the SeSe bonds enables a fast and large deformation occurring during the phase transition. Meanwhile, the different SeSe bonding states in α‐, α ′‐, β‐Ag2 Se phases lead to the formation of a large number of nanoslabs and the high concentration of dislocations at the interface, which flexibly accommodate the strain caused by the phase transformation. This study reveals the atomic mechanism of the deformation in Ag2 Se inorganic semiconductors during the phase transition, which also provides inspiration for understanding the phase transition process in other functional materials. Abstract : The SeSe bonds are folded when the Ag + ‐ion vacancies are ordered and become stretched when these vacancies are disordered. Such a stretch/fold of the SeSe bonds enables a fast and large deformation occurring during the phase transition. A new ordered high‐temperature phase of α ′‐Ag2 Se acts as a buffer to flexibly accommodate the stress caused by the phase transformation.